An evaluation of the quality customer service delivered by Eskom to rural household customers in the Eastern Cape - Myoli, Mncedi Eric (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
[Abstract - Conclusion]: This research study confirms the theory in the literature review on delivery of quality service to customers and premise that there is a statistically significant difference between Eskom service as perceived by rural prepaid household customers and their expectations. This study also highlights the need for Eskom management to take into cognisance the unique rural prepaid customer service needs and how to meet them, perhaps a differentiated service approach rather than a one-strategy-fits-all approach. This is in view of gaps created between expectations and perceptions of service, especially in the reliability dimension that could require a concentrated or changed performance approach to close them.
Keywords: Eskom (Firm); Electric power distribution -- South Africa -- Eastern Cape; Electric power distribution -- Customer services -- South Africa -- Eastern Cape; Electric power distribution -- South Africa -- Eastern Cape -- Quality control; Consumer satisfaction -- South Africa -- Eastern Cape -- Evaluation; Customer services -- Rating of -- South Africa -- Eastern Cape; Rural electrification -- South Africa -- Eastern Cape